Typological provided equipment features of qualifications weightlifters clean and jerk. - Tovstonoh A.F (Kharkov National Pedagogical University, 2011)
The article presents the scientific data on kinematic characteristics of qualifications weightlifters of different figure tipes in clean and jerk. In particular, the differences in speed, duration and trajectory of a jolt, as well as in terms of phases of weightlifters clean and jerk of different figure types. Set typological provided equipment features of weightlifters in lifting barbell on his chest and push from the chest.